ANALYSIS OF THE USE OF ROY'S ADAPTATION NURSING THEORY IN HEART DISEASE PATIENTS - Syafriati, Ani; Rivana, Eka (Journal of Nursing Culture and Technology, 2025)
Background: The heart as an important organ cannot be protected from diseases that can attack it. One of the deadliest diseases in the world is heart attack. Objective: This research aims to determine the behavioral response of heart disease patients which gives rise to individual adaptive responses to maintain individual adaptation in heart disease patients. Method: This research uses a qualitative method with a qualitative descriptive approach. The sampling technique is purposive sampling. Data collection methods were in-depth interviews and observation sheets from Calista Roy. Data analysis using the content analysis method. The informants in this study with heart disease in the Siloam Hospital Palembang Inpatient Room were 4 people (2 men, 2 women) and 1 Key Informant. Results: The results of this study emerged 7 themes, namely lack of knowledge about heart disease, signs and symptoms felt by patients, heart patients' efforts to treat their disease, compliance with treatment regimens, healthy diet and lifestyle, obstacles in maintaining their health, and hospital facilities and actions for heart disease patients. The research results show that there is an adaptive response from heart disease patients which can improve patient integrity and be able to carry out activities that are favorable to survival. However, it was still found that participants lacked knowledge regarding their disease, so there was still non-compliance with the treatment regimen. Conclusions: The use of Roy's adaptive nursing theory in providing nursing care to patients with heart disease makes it easier for nurses to detect the patient's situation in adapting to heart disease.